(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2021)
The purpose of this research was to examine the impact of the diversity of conceptions applicable according to the development of the civil process and the precautionary process in Venezuela. For the analysis of the phenomenon, national and foreign civil adjective norms were used, as well as the Constitution of the Bolivarian Republic of Venezuela (1999), doctrinal positions and jurisprudential criteria of the Supreme Court of Justice. This research had a documentary design, using the dialectic method for the interpretation of the phenomenon. It was concluded that the legal nature of the precautionary process is circumscribed to the theory of it as a dynamic juridical situation.